Fissure Grouting Mechanism Accounting for the Time-Dependent Viscosity of Silica Sol - Zhang, Weijie; Yang, Fei; Han, Chenghao; Ren, Qian; Peng, Ziyu; Wu, Fangxiao; Zhang, Zhenyong (ACS omega, 2021)
Subject to the complex hydrogeological environment where underground engineering is located, the grouting prevention and control of microfissure water ingress are increasingly strict. Silica sol grout has been increasingly used in field tests because of its fine particles and good injectability. Therefore, it is necessary to examine the time-dependent viscosity of silica sol grout and clarify its diffusion law in a rock fissure. In this study, the time dependence of the viscosity of silica sol grout was studied, and then the grout viscosity was subdivided into a slow growth period, accelerated growth period, and rapid curing period according to the growth rate. The effects of the concentration of colloidal silica suspension, the concentration of accelerant, and the mixing volume ratio of the two on the growth of the slurry viscosity were studied. A parameter λ was introduced to comprehensively characterize the influence of the three factors on the rheological properties of the slurry. The relationship between the gel induction time and λ and the accelerating growth stage of the slurry gel was obtained by data fitting. The time-dependent equation of the silica sol solution was established. The difference in the grouting diffusion law between silica sol grout and cement–sodium silicate grout (C-S grout) is compared and analyzed by a stepwise calculation method under two grouting modes (constant-pressure grouting and constant-rate grouting). The results show that under the condition of constant-pressure grouting, the silica sol grout migrates and diffuses continuously for a long time, while the C-S grout is close to the final diffusion form at 15–20 s, and the maximum diffusion distance is much smaller than that of silica sol grout. Under the condition of constant-rate grouting, the grouting pressure driving C-S grout increases sharply with time. Compared with C-S grout, silica sol grout has the obvious advantages of a longer effective diffusion time and lower energy consumption. The research results have certain theoretical significance and reference value for the engineering design of silica sol grouting.